Phosphorus status of five wetlands in Edo State - Edosomwan, Lawrence Nosa; Agbogun, Lucky; Agbonifo, Patience Osariemen (Jurnal Ilmu Pertanian, 2024)
This experiment was performed to determine the phosphorus levels in certain wetland soils in Edo State, Nigeria. Soil samples were collected from five wetlands at two depths: 0–15 cm and 15–30 cm. The samples were air-dried, sieved, and analyzed to ascertain the physical and chemical properties of the soils using standard laboratory techniques. The findings indicated that the majority of soil pH levels were slightly acidic, ranging from 6.6 to 7.0 (neutral), with the exception of soils from Obiemen, Agwa, and Benin, which exhibited moderate acidity (4.2–4.8). Soils from Irrua (Obiemen and Agwa) and Benin (Ikpoba Okha) demonstrated elevated phosphorus content, with a P range of 11.41–15.70 mg/kg, whereas soils from Ekpoma (Opoji), Benin (Oka-Naruovia), and Benin (Orhiomwon) exhibited low phosphorus levels, ranging from 2.88 to 5.56 mg/kg. There was a direct relationship between soil pH and the available phosphorus content. Therefore, there is need to augment the soils with P-fertilizers for increase crop productivity.